Organizational culture analysis, agile leadership, self-efficacy and work motivation on strengthening organizational commitment - Purwaningsih, Dewi; Setyaningsih, Sri; Wulandari, Dian (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Organizational commitment in educational institutions remains a critical issue, particularly in understanding how organizational and individual psychological factors shape teachers’ attachment to their organizations. Empirical findings on the roles of organizational culture, agile leadership, and self-efficacy, however, remain inconsistent, especially in vocational education. This study examifnes the relationships among these variables, including the mediating role of work motivation. A quantitative explanatory approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to data collected from 195 teachers of private vocational high schools in West Jakarta. The results show that organizational culture and work motivation have significant positive relationships with organizational commitment. Organizational culture also has a significant indirect effect through work motivation. Self-efficacy has no significant direct relationship with organizational commitment but shows a significant indirect effect via work motivation. In contrast, agile leadership does not demonstrate significant direct or indirect relationships. These findings indicate that organizational commitment is more closely associated with cultural and psychological factors than with leadership style. This study highlights the role of work motivation as a key mediating mechanism linking organizational and individual factors in the educational context.